Influence of Advertising Expense and Cost of Room Sold on Room Revenue in ISBD - K W Angga; I N Subratha; I M Wijana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
Ibis Style Bali Denpasar room revenue has decreased over the past 3 years despite having issued advertising Charges and set the appropriate room rates but room revenue is still not maximal. This study aims to determine the effect of Advertising Expenses and Room Sales Cost on Room Revenues at Ibis Style Bali Denpasar. The independent variables used in this study are Advertising Expenses and Room Sales Cost and for the dependent variable in this study is Room Revenue. The research method used is classic assumption test, correlation analysis, determination analysis, multiple linear regression analysis, t test and f test by using the help of the SPSS 24.0 program. Based on the results of the study and the results of data analysis, the variable advertising costs affect room revenue, which shows the results of the t-count value of 4.909 is greater than the t-table of 1.68 with t-count in the rejection area h0 means h0 is rejected and ha is accepted . The cost of room sales affects the room income which shows the results of the t-count value of 1.967 greater than t-table of 1.6 with t-count in the rejection area h0 means that h0 is rejected and ha is accepted. Advertising expenses and room sales costs of room revenue have an F-count value of 52.073 greater than f-table of 2.42 with f-count being in the rejection area h0 means that h0 is rejected and ha is accepted. The coefficient of determination shows a value of 0.698, this shows that the advertising burden and cost of room sales are partially and simultaneously contributing 69.8% to room revenue. From the explanation above, it can be concluded that there is an influence between advertising expenses and room sales cost of rooms on room revenues both partially and simultaneously. Thus, the hotel is expected to pay more attention to advertising spending and ensure that the room price is appropriate because it affects the room revenue obtained by the hotel.